2003
DOI: 10.1523/jneurosci.23-09-03837.2003
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Expression in Corticothalamic Efferents Reveals a Developmental Role for Nicotinic Acetylcholine Receptors in Modulation of Passive Avoidance Behavior

Abstract: Prenatal nicotine exposure has been linked to attention deficit hyperactivity disorder and cognitive impairment, but the sites of action for these effects of nicotine are still under investigation. High-affinity nicotinic acetylcholine receptors (nAChRs) contain the beta2 subunit and modulate passive avoidance (PA) learning in mice. Using an inducible, tetracycline-regulated transgenic system, we generated lines of mice with expression of high-affinity nicotinic receptors restored in specific neuronal populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 45 publications
5
65
0
Order By: Relevance
“…Even though we cannot rule out subtle effects of nicotine on placental or brain vascular integrity, which may indirectly impair brain development, it seems more likely that the abnormal behavior observed in PNE mice was caused by the pathological activation of acetylcholine nicotinic receptors (AchNR) during early stages of brain development (Slotkin, 1998;Slotkin, 2004). Consistent with this interpretation, a recent study suggests that the normal activation of AchNR located in cortico-thalamic terminals plays a critical role in the development of neural circuits involved in the regulation of normal fear-associated learning (King et al, 2003). In this study, knocking-out the b2 subunit of these receptors in neonatal, but not adult, mice resulted in increased learning of a fear-associated learning task known as passive avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we cannot rule out subtle effects of nicotine on placental or brain vascular integrity, which may indirectly impair brain development, it seems more likely that the abnormal behavior observed in PNE mice was caused by the pathological activation of acetylcholine nicotinic receptors (AchNR) during early stages of brain development (Slotkin, 1998;Slotkin, 2004). Consistent with this interpretation, a recent study suggests that the normal activation of AchNR located in cortico-thalamic terminals plays a critical role in the development of neural circuits involved in the regulation of normal fear-associated learning (King et al, 2003). In this study, knocking-out the b2 subunit of these receptors in neonatal, but not adult, mice resulted in increased learning of a fear-associated learning task known as passive avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinic currents have also been reported in low-threshold spiking interneurons in layers II/III and V of visual cortex in young rats (Xiang et al, 1998), and of prefrontal cortex in young mice (Couey et al, 2007). It has been shown that knock-out mice deleted for all ␤2-containing nicotinic receptors have deficits in cortically mediated arousal processes (Granon et al, 2003;King et al, 2003;Cohen et al, 2005;Granon and Changeux, 2006). Interestingly, it has been found that the performance of these mice on a behav- ioral task of arousal can be normalized if ␤ 2 subunits are restored in corticothalamic neurons during the first 3 weeks of postnatal development (King et al, 2003).…”
Section: Developmental Changes In Layer VI Nicotinic Receptorsmentioning
confidence: 99%
“…During this time, there is a marked band of high-affinity nicotinic binding in layer VI in the prefrontal cortex (Tribollet et al, 2004), the primary location of corticothalamic neurons. Recent transgenic work shows that nicotinic receptors are expressed by corticothalamic neurons and are present in corticothalamic terminals in mice (King et al, 2003). Nicotinic acetylcholine receptors have been suggested to play a trophic role in the development of cortical neurons and brain circuitry (Belluardo et al, 1999;Brown and Kolb, 2001;Liang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine administration during the early postnatal period in the rodent disrupts auditory learning and nicotinic regulation of primary auditory cortex (Hsieh et al, 2002;Liang et al, 2006). High-affinity nAChRs expressed on corticothalamic efferents during development are critical for normal passive avoidance learning (King et al, 2003). Stimulation of nAChRs by nicotine may also alter timing of the switch in action of GABA from excitation to inhibition, which may disrupt circuit development (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%